Thermal Overload Relay Trainer Design for Electric Motor Control Practice - Ilham, Muhammad; Rizal Fachri, Muhammad; Baihaqi, Baihaqi (PTE FTK UIN Ar-Raniry, 2026)
The limited availability of adequate practical learning media often poses a significant challenge for students in understanding the applied principles of electrical components, particularly the Thermal Overload Relay (TOR). This study aims to design, develop, and evaluate the feasibility of a TOR trainer as an innovative learning medium for electric motor control practicum. The research methodology employed is Research and Development (R&D), adapting the 4D development model (Define, Design, Develop, Disseminate), which was limited to the development stage. Data were collected using Likert-scale validation instruments involving media and subject matter experts. The analytical results indicate that the TOR trainer obtained an average validation score of 4.2, categorized as